Eosinophilic pancreatitis presenting as possible malignancy. Issue 4 (4th July 2021) - John, Rebekah; Yanchak, Theresa; Ramirez, Jonathan
Abstract: Eosinophilic pancreatitis is a rare form of chronic pancreatitis that is often mistaken for malignancy due to nonspecific presenting symptoms and noncontributory auxiliary exams. This clinical case report highlights a unique presentation of chronic pancreatitis. A middle-aged man developed abdominal pain, and repeat imaging showed an interval increase in size of a known pancreatic lesion. A core biopsy showed benign pancreatic tissue with eosinophilic-rich inflammation; IgE levels were also elevated. The patient was started on a prednisone taper, and repeat computed tomography 3 months later showed a decreased size of the pancreatic lesion. Correct and timely diagnosis of eosinophilic pancreatitis may avoid invasive unnecessary surgical procedures and allow for earlier initiation of appropriate therapy.